1992
DOI: 10.1002/mrd.1080310407
|View full text |Cite
|
Sign up to set email alerts
|

Hemizona assay for measuring zona binding in the lowland gorilla

Abstract: The hemizona assay is a diagnostic test used to evaluate the binding potential of spermatozoa to zonae pellucida and has been used to predict fertilization potential in the human. In this study, frozen-thawed gorilla spermatozoa were coincubated with human hemizonae to evaluate tight binding and to assess the use of human zonae in evaluating sperm fertility. Matching hemizonae were incubated with human sperm to serve as a control. For evaluation of binding studies in a homologous system, matching halves of gor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
(11 reference statements)
1
16
1
Order By: Relevance
“…Others have shown that human sperm can bind to and penetrate the zona of gibbon and gorilla oocytes, the only exceptions for the human male gamete other than its homologous zona pellucida (Bedford, 1977;Yanagimachi, 1988;Liu et al, 1991;Lanzendorf et al, 1992). On the other hand, it has been shown that gorilla, marmoset and horse sperm can bind to the zona pellucida of salt-stored human oocytes (Liu et al, 1991;Lanzendorf et al, 1992). Here, we have not observed binding of cynomolgus monkey sperm to the human zona pellucida.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Others have shown that human sperm can bind to and penetrate the zona of gibbon and gorilla oocytes, the only exceptions for the human male gamete other than its homologous zona pellucida (Bedford, 1977;Yanagimachi, 1988;Liu et al, 1991;Lanzendorf et al, 1992). On the other hand, it has been shown that gorilla, marmoset and horse sperm can bind to the zona pellucida of salt-stored human oocytes (Liu et al, 1991;Lanzendorf et al, 1992). Here, we have not observed binding of cynomolgus monkey sperm to the human zona pellucida.…”
Section: Discussioncontrasting
confidence: 63%
“…Cynomolgus monkey sperm had a very low binding affinity to the human zona, although they showed a slightly higher rate of acrosome reactions on the heterologous (human) zonae. Others have shown that human sperm can bind to and penetrate the zona of gibbon and gorilla oocytes, the only exceptions for the human male gamete other than its homologous zona pellucida (Bedford, 1977;Yanagimachi, 1988;Liu et al, 1991;Lanzendorf et al, 1992). On the other hand, it has been shown that gorilla, marmoset and horse sperm can bind to the zona pellucida of salt-stored human oocytes (Liu et al, 1991;Lanzendorf et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of non‐species‐specific gamete binding and penetration have been observed previously using different combinations of mammalian sperm and oocytes (Bedford, 1977; Yoshimatsu et al, 1988; Liu et al, 1991; Cox, 1992; Lanzendorf et al, 1992; Oehninger et al, 1993).…”
Section: Discussionsupporting
confidence: 60%
“…These results are consistent with the concept that no selection pressure for species-specific binding exists in the murine reproductive system. In contrast to the avid binding to heterologous eggs shown by the epididymal sperm of mice and some other mammals, human sperm do not bind to foreign eggs except those of some other hominoids like the gibbon (37) and the lowland gorilla (58). The selection pressure that created this taxon-specific binding of human sperm is currently unknown.…”
Section: Why Continue To Employ Carbohydrate Recognition For Murine Gmentioning
confidence: 94%